2023
DOI: 10.3390/ijerph20032055
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Lifestyle of Pediatric Healthcare Professionals during the COVID-19 Pandemic

Abstract: The objective of this study was to analyze the association between sociodemographic and occupational variables with the lifestyle of health professionals in pediatric units during the COVID-19 pandemic. A cross-sectional study was conducted with 407 health professionals working in four pediatric health units in the State of Bahia, northeast Brazil. The Fantastic Lifestyle Questionnaire and a questionnaire with sociodemographic and employment variables self-applied via Google Forms were used. The final binary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Coutinho et al [73] examined the relations between sociodemographic factors and the lifestyle of people working in pediatric units in Bahia, Brazil, during COVID-19. The study revealed that people who were not married received 3-5 minimum wages, and that those with more than one job were more likely to follow dangerous lifestyle behaviors.…”
Section: Health Issuesmentioning
confidence: 99%
“…Coutinho et al [73] examined the relations between sociodemographic factors and the lifestyle of people working in pediatric units in Bahia, Brazil, during COVID-19. The study revealed that people who were not married received 3-5 minimum wages, and that those with more than one job were more likely to follow dangerous lifestyle behaviors.…”
Section: Health Issuesmentioning
confidence: 99%